Virtual Reality-Based Exercise Rehabilitation in Cancer-Related Dysfunctions: Scoping Review - Zhenzhen Su; Liyan Zhang; Xuemin Lian; Miaomiao Guan (JMIR Publications, 2024)
BackgroundVirtual reality-based exercise rehabilitation (VRER) is a promising intervention for patients with cancer-related dysfunctions (CRDs). However, studies focusing on VRER for CRDs are lacking, and the results are inconsistent. ObjectiveWe aimed to review the application of VRER in patients with CRDs. MethodsThis scoping review was conducted following the PRISMA-ScR (Preferred Reporting Items for Systematic Reviews and Meta-Analyses extension for Scoping Reviews) checklist framework. Publications were included from the time of database establishment to October 14, 2023. The databases were PubMed, Embase, Scopus, Cochrane, Web of Science, ProQuest, arXiv, IEEE Xplore, MedRxiv, CNKI, Wanfang Data, VIP, and SinoMed. The population included patients with cancer. A virtual reality (VR) system or device was required to be provided in exercise rehabilitation as an intervention. Eligible studies focused on VRER used for CRDs. Study selection and data extraction were performed by 2 reviewers independently. Extracted data included authors, year, country, study type, groups, sample size, participant age, cancer type, existing or potential CRDs, VR models and devices, intervention programs and durations, effectiveness, compliance, satisfaction, and safety. ResultsWe identified 25 articles, and among these, 12 (48%) were randomized clinical trials, 11 (44%) were other experimental studies, and 2 (8%) were observational studies. The total sample size was 1174 (range 6-136). Among the 25 studies, 22 (88%), 2 (8%), and 1 (4%) included nonimmersive VR, immersive VR, and augmented reality, respectively, which are models of VRER. Commercial game programs (17/25, 68%) were the most popular interventions of VRER, and their duration ranged from 3 to 12 weeks. Using these models and devices, VRER was mostly applied in patients with breast cancer (14/25, 56%), leukemia (8/25, 32%), and lung cancer (3/25, 12%). Furthermore, 6 CRDs were intervened by VRER, and among these, postmastectomy syndromes were the most common (10/25, 40%). Overall, 74% (17/23) of studies reported positive results, including significant improvements in limb function, joint range of motion, edema rates, cognition, respiratory disturbance index, apnea, activities of daily living, and quality of life. The compliance rate ranged from 56% to 100%. Overall, 32% (8/25) of studies reported on patient satisfaction, and of these, 88% (7/8) reported satisfaction with VRER. Moreover, 13% (1/8) reported mild sickness as an adverse event. ConclusionsWe found that around half of the studies reported using VRER in patients with breast cancer and postmastectomy dysfunctions through nonimmersive models and commercial game programs having durations of 3-12 weeks. In addition, most studies showed that VRER was effective owing to virtualization and interaction. Therefore, VRER may be an alternate intervention for patients with CRDs. However, as the conclusions were drawn from data with acknowledged inconsistencies and limited satisfaction reports, studies with larger sample sizes and more outcome indictors are required.